Effect of Allium sativum and Nigella sativa on alleviating aluminum toxicity state in the albino rats - Abdel Ghfar, Sayed Soliman; Ali, Montaser Elsayed; Momenah, Maha Abdullah; Al-Saeed, Fatimah A.; Al-Doaiss, Amin A.; Mostafa, Yasser Sabry; Ahmed, Ahmed Ezzat; Abdelrahman, Mohamed (Frontiers in Veterinary Science, 2022)
The study objective was to evaluate Allium sativum's potential and Nigella Sativa's combination's potential to reduce aluminum toxicity and return to the normal state. In the present study, a hundred albino rats were randomly divided into five equal groups. The first group was used as a control group; the other four groups were exposed to aluminum 1,600 ppm. The second exposed to aluminum only; the third and fourth groups were treated with Allium sativum 5% and Nigella sativa 5%, respectively, while the fifth group was treated with a mix of Allium sativum 2.5% and Nigella sativa 2.5% for 8th weeks. After 8 weeks, the aluminum administration was stopped, and the second group was divided into three groups. The groups were treated with Allium sativum 5% and Nigella sativa 5%, and a mix of Allium sativum 2.5% and Nigella sativa 2.5%, respectively. The first group was the control group (continued from the first experiment). Garlic and Nigella sativa were crushed and added to feed while receiving aluminum chloride daily at a dose of 1.6 ml/l was added to the drinking water. Histopathological changes in the liver, kidney, and testes were investigated after 8 and 16 weeks, and blood samples were collected after 4, 8, and 16 weeks for biochemical blood parameters. The results showed that the histopathological examination of the liver, kidney, and testes showed signs of congestion in blood vessels after aluminum exposure. Meanwhile, the treatment with Allium sativum or Nigella sativum or the mixture between them had positive effects on evading the harmful effects of aluminum in the liver, Kidney, and testes tissues. In addition, there were protective effects for Allium sativum and Nigella sativa against aluminum on serum creatinine, urea, ALT, and AST concentrations. The present study concluded that supplementation with Allium sativum or Nigella sativa or their combination could reduce aluminum toxicity and return the liver, kidney, and testes to normal.